Incidencias socioambientales del proyecto minero Mirador en la cordillera del Cóndor en Ecuador (Tema Central) - Espinosa Quezada, María Gabriela (2025)
In 2012, a new phase of mining industrialization began, with the Mirador mining project becoming the center of attention and debate as the first large-scale project of direct interest to the Ecuadorian government. From a retrospective point of view, it has been the focus of different conflict scenarios, which makes it possible to visualize the main sociolegal actions as a response mechanism of the local populations to the imposed extractivist model. The objective of this paper is to expose the socio-environmental impacts of this project. The approach is retrospective and the methodology used is qualitative, where the review of documents, videos and interviews were crucial. The results reveal scenarios of high conflict and socio-legal actions in relation to the protection of constitutional rights by the local population, who were the main factors of resistance and defense of nature. It is concluded that there is a rupture of the internal social fabric as part of the mining metabolism.